Organization and transcriptional regulation of Drosophila Na(+), K(+)-ATPase beta subunit genes: Nrv1 and Nrv2. - Xu, P.; Sun, B.; Salvaterra, P.M. (Gene, 1999)
Drosophila melanogaster has two Na(+),K(+)-ATPase beta subunit genes (Nervana 1 and 2; Nrv), with tissue-specific expression patterns. Nrv1 produces a single beta subunit isoform expressed primarily in muscle tissue, whereas Nrv2 codes for two different isoforms (2.1 and 2.2) expressed in the nervous system. We have determined the complete molecular genomic organization for both Nrv genes. Only 3kb of DNA separate the 3' end of Nrv2 from Nrv1. The cDNAs from all three forms of Nrv have been mapped onto the genomic structure and all intron-exon junctions have been confirmed by direct sequencing. The genomic DNA positioned in the 5' flanking region of each Nrv gene has also been tested for tissue-specific transcriptional regulatory activity. P-element transformation vectors were constructed, which contained either 7.7kb of Nrv2 or 3.5kb Nrv1 5' flanking DNA driving expression of a lacZ reporter gene. Multiple transgenic Drosophila lines were established for each construct and analyzed for their beta-galactosidase expression pattern. The tissue-specific expression of each Nrv gene is independently regulated by the cis-element(s) present in the 5' flanking region. The Nrv2 5' flanking DNA directs expression exclusively to the nervous system, whereas Nrv1 5' flanking DNA directs expression primarily in muscle tissue.